ENHANCING THE ADOPTION OF ICT IN TEACHING AND LEARNING: EXPLORING KEY FACTORS IN NIGERIAN UNIVERSITIES - Mohammed Salisu, Isyaka; Alhaji Abubakar, Aliyu; Samaila Danbauchi, Ezra (African Journal of Social and Behavioural Sciences, 2024)
This study investigates the factors influencing the successful adoption of Information and Communication Technology (ICT) in teaching and learning at Nigerian universities. Using Partial Least Square-Structural Equation Modelling (PLS-SEM), we analysed data from 3,218 respondents across 12 Nigerian universities to examine the relationship between key constructs—such as attitude, infrastructure, ICT training, usage, professional development, and quality of ICT resources—and ICT adoption. The results reveal that a positive attitude toward ICT, its active usage, and the quality of technological resources significantly impact successful ICT adoption, with beta values of 0.076, 0.422, and 0.046, respectively. However, organisational factors such as infrastructure, ICT training, and professional development were not found to be significant contributors. These findings underscore the importance of fostering a positive attitude, enhancing ICT engagement, and ensuring the availability of high-quality technological resources to drive successful ICT adoption in Nigerian higher education. The study concludes that while technical factors are critical, further research is needed to explore how organisational support can be improved to bolster the adoption process.